2020
DOI: 10.1016/j.jstrokecerebrovasdis.2020.104989
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous thrombosis: Atypical presentation of COVID-19 in the young

Abstract: Objective: Identify clinical and radiographic features of venous infarct as a presenting feature of COVID-19 in the young. Background: SARS-CoV-2 infection causes hypercoagulability and inflammation leading to venous thrombotic events (VTE). Although elderly patients with comorbidities are at higher risk, COVID-19 may also cause VTE in a broader patient population without these risks. Neurologic complications and manifestations of COVID-19, including neuropathies, seizures, strokes and encephalopathy usually o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 18 publications
3
112
1
4
Order By: Relevance
“…23 patients had ICH and 24 patients had ischemic stroke. Among the COVID-19 patients with ICH, 19 (69.6%) patients had lobar hemorrhage, which was significantly high compared to the number of patients with non-lobar hemorrhage (7 [30.4%]) Retrospective Iran Behzadnia et al [ 112 ] Hemorrhagic lesions and white matter microhemorrhages in 30% and 24% of 37 COVID-19 patients presenting with neurological manifestations with relevant abnormal brain MRI, respectively Retrospective France Kremer et al [ 30 ] Bilateral basal ganglia hemorrhage Case report Iran Haddai et al (2020) [ 113 ] Immune thrombocytopenic purpura—SAH Case report France Zulfiqar et al (2020) [ 114 ] Vasculitis Case report France Hanafi et al (2020) [ 115 ] Cerebral venous sinus thrombosis Case report UK Hughes et al (2020) [ 116 ] Cerebral venous thrombosis Case report USA Klein et al [ 117 ] Venus thromboembolism was seen in 36% and ischemic stroke in 2.5% of 388 patients Retrospective Italy Lodigiani et al [ 118 ] Silent hypoxemia Attributable to the brain infection and subsequent dysfunction of breathe controlling centers in cortical regions rather than subcortical structures and the brain stem Commentary NA Coen et al (2020) [ 120 ] White matter and globus pallidum inflammatory lesions CT scan of the brain demonstrated hypodense lesions involving supratentorial white matter and pallidum bilaterally. MRI showed bilateral but asymmetrical lesions with periventricular and deep white matter involvement Case report France Brun et al (2020) [ 147 ] Neuroleptic malignant syndrome Haloperidol decanoate use 3 weeks prior to admission Case report USA Kajani et al (2020) [ 127 ] Steroid responsiv...…”
Section: Discussionmentioning
confidence: 99%
“…23 patients had ICH and 24 patients had ischemic stroke. Among the COVID-19 patients with ICH, 19 (69.6%) patients had lobar hemorrhage, which was significantly high compared to the number of patients with non-lobar hemorrhage (7 [30.4%]) Retrospective Iran Behzadnia et al [ 112 ] Hemorrhagic lesions and white matter microhemorrhages in 30% and 24% of 37 COVID-19 patients presenting with neurological manifestations with relevant abnormal brain MRI, respectively Retrospective France Kremer et al [ 30 ] Bilateral basal ganglia hemorrhage Case report Iran Haddai et al (2020) [ 113 ] Immune thrombocytopenic purpura—SAH Case report France Zulfiqar et al (2020) [ 114 ] Vasculitis Case report France Hanafi et al (2020) [ 115 ] Cerebral venous sinus thrombosis Case report UK Hughes et al (2020) [ 116 ] Cerebral venous thrombosis Case report USA Klein et al [ 117 ] Venus thromboembolism was seen in 36% and ischemic stroke in 2.5% of 388 patients Retrospective Italy Lodigiani et al [ 118 ] Silent hypoxemia Attributable to the brain infection and subsequent dysfunction of breathe controlling centers in cortical regions rather than subcortical structures and the brain stem Commentary NA Coen et al (2020) [ 120 ] White matter and globus pallidum inflammatory lesions CT scan of the brain demonstrated hypodense lesions involving supratentorial white matter and pallidum bilaterally. MRI showed bilateral but asymmetrical lesions with periventricular and deep white matter involvement Case report France Brun et al (2020) [ 147 ] Neuroleptic malignant syndrome Haloperidol decanoate use 3 weeks prior to admission Case report USA Kajani et al (2020) [ 127 ] Steroid responsiv...…”
Section: Discussionmentioning
confidence: 99%
“…Another series by Avula et al reported four patients with ischemic stroke and COVID two of them had large vessel occlusion [ 1 ]. Patients with severe COVID-19 infection have noted to develop a hyperinflammatory state followed by a prothrombotic state that is frequently complicated by both venous and arterial thromboembolism [ 15 , 16 ]. Simultaneous multiple LVO of different vascular territories has been consistently reported and was postulated to be secondary to the prothrombotic state induced by COVID-19 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heparin interacts with may pro-in ammatory and procoagulant cascades to prevent in ammation and coagulopathy associated with sepsis (39). The use unfractionated heparin and LMWH are used in acute CSVT (9). The use of tissueplasminogen activator (t-PA) brinolytic therapy were used in decompensated patients with no options for escalation of care (40).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports show the cerebral venous thrombosis related to COVID-19 with variant presentation (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%